On Some Evidences of Natural Selection for Drought Resistance in Pinus oocarpa Schiede provenances - Kandy, A K; Ventor, C R; Mullerstael, H (Annals of Arid Zone, 2016)
In a nursery test of 11 provenances of P. oocarpa it was found that provenances 3/71, 4/71, 8/71 and 9/71 which are native of comparatively drier areas have certain characteristic features which suggest that these provenances have undergone natural selection for drought resistance capacity. It is presumed that presence of shorter. fewer. lighter but more succulent primary needles and larger roots in these provenances than those of the other ones is an ecological adaptation to the drier climatic conditions and has apparently taken place in a long term during evolution and is represented in various degrees in different provenances probably due to the natural selection. Tests for survival of seedlings in induced drought conditions should support this assumption.